NATIONALISM IN BAKASIR'S POEM 'INDUNISIYYAA KUBRAA LANAA': A SOCIOLOGY OF LITERATURE PERSPECTIVE - Wahyu Hanafi Putra (Leksema: Jurnal Bahasa dan Sastra, 2022)
This study aimed to describe the thoughts and attitudes of nationalism expressed by Ali Ahmad Bakasir in his poem Indunisiyyā Kubrā Lanā by using sociological approach to literature. The primary data of this research were the book entitled Indūnisiyya: Malhamah al-Ḥubb was al-Ḥuryah fī Hayāti. The data were collected by documentation, whereas the analysis employed dialectical method. The results showed that Bakasir, as an Indonesian-Middle Eastern Arabic writer, has his anxiety and love to Indonesia expressed in the form of prose, poetry, and drama. In addition, the Arabic literary works written by Bakasir, particularly those with Indonesian theme, are heavily influenced by sociological aspects. As he was born in Indonesia, Bakasir has a high attitude toward nationalism, even though he does not currently live in Indonesia. A lot of his works of prose, poetry, and drama with the theme of Indonesia were written in hyperbolic expression, such in the poem Indūnisiyyā Kubrā Lanā that is included in the book Indūnisiya: Malhamah al-Ḥubb was al-Ḥuryah fī Hayāti.